A new model for cadastral surveying using crowdsourcing. Issue 359 (4th March 2018) - Apostolopoulos, K.; Geli, M.; Petrelli, P.; Potsiou, C.; Ioannidis, C.
Abstract : A 'fit-for-purpose' approach is developed, tested and presented for cadastral surveys through increased owners' participation using new technology and m-government services. Three case studies are reported, for urban, suburban and rural areas, with a combined use of two mobile applications: a commercial software package (ESRI's Collector for ArcGIS ) and an opensource self-developed application named BoundGeometry . The parameters of time, quality and accuracy are assessed and the identified difficulties are classified. It is concluded that the method is applicable both in developed and developing countries, and each time adjustable to the available infrastructure.